DINAMIKA DAN STRUKTUR PENGETAHUAN DALAM TRANSISI ENERGI BERKELANJUTAN: PENDEKATAN BIBLIOMETRIK - Nazwa Alya; Muhammad Irfan Syahputra; Ridwan Arjuna (LENVARI, 2026)
This study examines the dynamics and knowledge structure of sustainable energy transition research using a bibliometric approach based on global data. A total of approximately 2,000 documents indexed in Scopus from 2021 to 2026 were analyzed using VOSviewer and Bibliometrix. The results reveal a significant increase in publications, indicating rapid development and growing global attention to energy transition issues. The knowledge structure is clustered into four main areas: energy technology systems, advanced energy materials, economic and policy aspects, and environmental sustainability. Renewable energy emerges as the most dominant theme, highlighting its central role in connecting various research domains. Despite this progress, challenges such as knowledge fragmentation and unequal global research contributions remain. This study provides comprehensive insights into research trends, collaboration patterns, and thematic evolution, while identifying future research directions, including the integration of smart technologies, interdisciplinary approaches, and data-driven energy policies to support a more effective and sustainable global energy transition.